2000
DOI: 10.1292/jvms.62.313
|View full text |Cite
|
Sign up to set email alerts
|

An Occurrence of Salmonella Typhimurium Infection in Sika Deer(Cervus nippon).

Abstract: ABSTRACT. Seven sika deer (Cervus nippon) in a herd of 30 deer in a park died. Upon examination of three dead deer, Salmonella Typhimurium was isolated from the organs and intestinal contents. Histopathological examination revealed catarrhal enteritis and focal necroses in the liver. Immunohistochemically, Salmonella antigen of O4 was detected in the enteric lesions. The case was diagnosed as S. Typhimurium infection in the sika deer. Because of the importance of Salmonella in public health, fecal and soil sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
14
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 15 publications
0
14
0
Order By: Relevance
“…Although cases of salmonellosis in farmed ungulates or park deer are reported worldwide, they seem to occur sporadically (Ecco, Guedes, Tury, Santos, & Perecmanis, 2006;Foreyt, Besser, & Lonning, 2001;French, Rodriguez-Palacios, & LeJeune, 2010;Perez et al, 1999;Sato, Kobayashi, Ichikawa, Kuwamoto, & Koyama, 2000). With respect to game birds, birds from pheasantries have higher prevalences of Salmonella than pheasants in the wild (Coburn, Snary, & Wooldridge, 2003).…”
Section: General Considerations About the Risk For Zoonoses And In Pmentioning
confidence: 99%
“…Although cases of salmonellosis in farmed ungulates or park deer are reported worldwide, they seem to occur sporadically (Ecco, Guedes, Tury, Santos, & Perecmanis, 2006;Foreyt, Besser, & Lonning, 2001;French, Rodriguez-Palacios, & LeJeune, 2010;Perez et al, 1999;Sato, Kobayashi, Ichikawa, Kuwamoto, & Koyama, 2000). With respect to game birds, birds from pheasantries have higher prevalences of Salmonella than pheasants in the wild (Coburn, Snary, & Wooldridge, 2003).…”
Section: General Considerations About the Risk For Zoonoses And In Pmentioning
confidence: 99%
“…A small outbreak of salmonellosis with significant mortality in captive elk (Cervus elaphus nelsoni) in the USA was due to a Salmonella enterica serovar Typhimurium DT104 strain, which was shown to be the multiple-drug-resistant epidemic strain common to cattle, sheep, and humans (Foreyt et al, 2001). Salmonella also were isolated from clinically ill captive and recently captured red deer calves (Cervus elaphus) in New Zealand (McAllum et al, 1978), captive sika deer (Cervus nippon) in Japan (Sato et al, 2000), and free-ranging, clinically ill Florida Key deer (O. v. clavium) (Nettles et al, 2002). However, previous attempts to identify Salmonella spp.…”
mentioning
confidence: 99%
“…For comparison, none of the five most frequently detected serovars in a national survey of beef cows in the USA were among the serovars most likely to cause clinical disease in humans or animals (Dargatz et al, 2000). Typhimurium (McAllum et al, 1978;Sato et al, 2000;Foreyt et al, 2001), Bovis-morbificans (McAllum et al, 1978), and Hartford, Weltevreden, and Kralendyl (Nettles et al, 2002) have been reported to cause disease in deer or elk. Oranienburg was recovered from two rumen samples from deer harvested by hunters on a university ranch (Branham et al, 2005).…”
mentioning
confidence: 99%
“…A partial list of non-mammalian wildlife that have been demonstrated to carry Salmonella and could potentially come in contact with feed sources and food production animals include toads, vultures, lizards, tree frogs, and wild passerine birds (Everard et al, 1979;Kapperud et al, 1998). A partial list of documented infected and / or carrier mammalian species include rats, mice, Sika deer, mongooses, bats, monkeys, and opossums (Thigpen et al, 1975;Everard et al, 1979;Henzler and Opitz, 1992;Singer et al, 1992;Sato et al, 2000). Domestic cats and companion animal facilities have also been shown to be problematic for Salmonella (Singer et al, 1992;van Immerseel et al, 2004a;Wright et al, 2005).…”
Section: Potential Risk Factors For Salmonella Feed Contaminationmentioning
confidence: 99%